2006
DOI: 10.1002/mrm.20959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cord motion on diffusion imaging of the spinal cord

Abstract: Measurement of diffusion and its dependence on direction has become an important tool for clinical and research studies of the brain. Diffusion imaging of the spinal cord may likewise prove useful as an indicator of tissue damage and axonal integrity; however, it is more challenging to perform diffusion imaging in the cord than in the brain. Here we report a study of the effects of motion on single-shot fast spin echo (FSE) diffusion tensor imaging (DTI) of the spinal cord. Diffusion imaging was performed at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…The discovery that lumbar and sacral spinal cord regions are essentially motionless has obvious and important implications for both structural and functional spinal cord imaging; namely, a region free of motion will also be free of motionrelated confounds, which are known to be problematic for both spinal fMRI and DTI in cervical regions. [16][17][18] Because the effects of motion will be significantly reduced, or even absent, in caudal spinal cord regions (compared with cervical regions), the sensitivity and selectivity of spinal fMRI methods can be evaluated under optimal in vivo conditions by using lower-body motor tasks or somatosensory stimulation to examine lumbar and sacral (instead of cervical) spinal cord ac- The black line indicates the cross-subject average of peak displacement, whereas the gray area indicates the region within 1 SD of the mean at each R/C position. To facilitate comparisons between cord motions in each direction (A/P and L/R), the scale has been normalized to that shown for the larger A/P displacements (plotted in Fig 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The discovery that lumbar and sacral spinal cord regions are essentially motionless has obvious and important implications for both structural and functional spinal cord imaging; namely, a region free of motion will also be free of motionrelated confounds, which are known to be problematic for both spinal fMRI and DTI in cervical regions. [16][17][18] Because the effects of motion will be significantly reduced, or even absent, in caudal spinal cord regions (compared with cervical regions), the sensitivity and selectivity of spinal fMRI methods can be evaluated under optimal in vivo conditions by using lower-body motor tasks or somatosensory stimulation to examine lumbar and sacral (instead of cervical) spinal cord ac- The black line indicates the cross-subject average of peak displacement, whereas the gray area indicates the region within 1 SD of the mean at each R/C position. To facilitate comparisons between cord motions in each direction (A/P and L/R), the scale has been normalized to that shown for the larger A/P displacements (plotted in Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…10,15 Several independent reports have also speculated about the magnitude and character of motion-related confounds in spinal fMRI and DTI experiments, but only recently have studies been undertaken to elucidate the specific effects of spinal cord motion and the extent to which this will probably hinder spinal fMRI and DTI. [16][17][18] Motion-compensated analysis of spinal fMRI data has revealed that cord motion decreases both the sensitivity and selectivity to neuronal function in the cervical and upper-thoracic regions of the spinal cord. 16 Likewise, for diffusion studies of rostral spinal cord segments, cardiac-gating at different time points of the heartbeat has revealed a strong dependence between the observed diffusion properties and cardiac phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Swallowing or related motion artifacts are mostly seen when imaging the cervical spinal cord. 10,11 Finally, in pediatric imaging especially, the possibility of increased subject motion makes obtaining accurate and reproducible DTI parameter values difficult. 12,13 Artifact-reducing techniques can be used to overcome some of these issues.…”
mentioning
confidence: 99%